Optimasi pH dan Waktu Kontak dalam Adsorpsi Methylene Blue dengan Ekstrak Kulit Rambutan - Sridevitri Sridevitri; Sri Benti Etika (MASALIQ, 2025)
The development of the textile industry in Indonesia produces hazardous waste, including toxic, carcinogenic, non-biodegradable Methylene Blue, which threatens aquatic ecosystems and human health. Adsorption is a simple and low-cost method widely used to reduce this pollution. This study aims to determine the effectiveness of flavonoid extracts from rambutan peel (Nephelium lappaceum L.) in adsorbing Methylene Blue, identify optimal adsorption conditions, and assess adsorption capacity. Analysis of the flavonoid extract using FTIR showed absorption peaks at 3265.13 cm-1 indicating O-H, at 2971.20 cm-1 indicating aliphatic C-H, and at 2280-2080 cm -1 detected C≡C or C≡N, at 1703.06 cm -1, C=O is detected at wavenumbers 1607.35 and 1519.01 cm-1, aromatic C=C is detected at wavenumbers 1446.51 and 1287.45 cm-1, C-O-C is detected at wavenumbers 1186.59 cm -1 detection of C-O-C or C-O-H bending at wavenumbers 874.50 and 751.93 cm-1 detection of aromatic C-H. The adsorption of Methylene Blue by flavonoid extracts is more consistent with the Langmuir isotherm, with a coefficient of determination (R) value of 0.996. The results of the study showed that the optimum conditions for Methylene Blue absorption occurred at pH 5 at 10.4825876 mg/g and at the optimum contact time of 80 minutes at 10.9669 mg/g.